Preliminary study on effect of agricultural activities in pollen spectrum of argentinean honey - Patrignani, Mariela (2019)
Honey floral origin is determined by the harversting region, but anthropogenic factors as agriculture expansion might modify the environmental flora and consequently honey floral origin. Argentina is one of the most important honey producers worldwide which, since the 1990s, has undergone an important agriculture transformation by the adoption of transgenic crops like soybean (Glycine max). However, little is known about the effects of this anthropogenic activity on the floral origin of honey or the statistical tools that could be used to analyse it. The objective of the present study was to evaluate the impact that these environmental modifications have on the pollen spectrum of honey. In order to achieve this, thirty-two samples of blossom honey were collected from three different ecoregions of the Buenos Aires province: Parana Delta and Islands, Espinal and Pampa, in two different years: 1999 and 2014. The pollen spectrum of honey samples was determined and the data obtained was analysed with multivariate statistical techniques. It could be concluded that the pollen composition of honeys from different ecoregions has significantly changed in the past years because of agriculture expansion and adaptation of transgenic crops (p=0.007). Honey samples harvested in 1999 were characterized by high values of Helianthus annuus, while in 2014 an important presence of Eryngium sp., Gleditsia triacanthos, Baccharis type, Trifolium sp. and Glycine max was observed. The present results show that honey palynological results and multivariate statistical analysis could be used as a preliminary attempt to evaluate environmental modifications.